Sensory deprivation in Staphylococcus aureus - Maite Villanueva (Nature Portfolio, 2018)
Bacteria use two-component systems (TCSs) to sense and respond to environmental changes. Here, the authors show that Staphylococcus aureus can survive in the absence of all its 16 TCSs under growth arrest conditions, and each TCS seems to be sufficient to sense and respond to specific environmental clues.